The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/rof/rfaa004
|View full text |Cite
|
Sign up to set email alerts
|

An Augmented q-Factor Model with Expected Growth*

Abstract: In the investment theory, firms with high expected investment growth earn higher expected returns than firms with low expected investment growth, holding investment and expected profitability constant. Building on cross-sectional growth forecasts with Tobin’s q, operating cash flows, and change in return on equity as predictors, an expected growth factor earns an average premium of 0.84% per month (t = 10.27) in the 1967–2018 sample. The q5 model, which augments the Hou–Xue–Zhang (2015, Rev. Finan. Stud., 28, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 307 publications
(91 citation statements)
references
References 88 publications
6
85
0
Order By: Relevance
“…That study proposed a two-coefficient model by adding an intercept coefficient alpha (α) to the original CAPM to represent the stock's expected excess return when the market risk premium is zero (α equals zero in an efficient market). Recent studies confirmed the alpha existed for the real stocks ( Barillas and Shanken, 2017 ; Fama and French, 1996b , 2015 ; 2018 ; Hou et al., 2015 , 2020b ; Hou et al., 2019 , 2020a ; Pham and Phuoc, 2020 ; Phuoc, 2018 ; Zhang, 2017 ). However, that study does not explore and capture other risks such as the firm's financial ratios and investment, stock momentum, and macroeconomic risks.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…That study proposed a two-coefficient model by adding an intercept coefficient alpha (α) to the original CAPM to represent the stock's expected excess return when the market risk premium is zero (α equals zero in an efficient market). Recent studies confirmed the alpha existed for the real stocks ( Barillas and Shanken, 2017 ; Fama and French, 1996b , 2015 ; 2018 ; Hou et al., 2015 , 2020b ; Hou et al., 2019 , 2020a ; Pham and Phuoc, 2020 ; Phuoc, 2018 ; Zhang, 2017 ). However, that study does not explore and capture other risks such as the firm's financial ratios and investment, stock momentum, and macroeconomic risks.…”
Section: Introductionmentioning
confidence: 81%
“…(2019) revised the by adding one more factor, the expected investment growth. Their new model, the ( Hou et al., 2020a , Hou et al., 2020b ), yielded strong explanatory power in the cross-section and outperformed the , FF5, FF6, and the Barillas and Shanken (2018) ' six-factor model in terms of maximum Sharpe ratio.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations